Analisis Kualitas Pelayanan yang Diberikan Koperasi Restu Berdikari Kecamatan Sungai Tebelian Kabupaten Sintang - devi yasmin; Supriyadi Sup (JURNAL MANAJEMEN MOTIVASI, 2013)
This study discusses the quality of service given the blessing of self-sustained cooperative Sungai Tebelian Kabupaten Sintang. This study aims to determine the quality of service that includes tangible dimension, reliability, responsiveness, assurance and empathy. This type of research used in this research is the survey method. Data collection techniques are the primary data, interviews, questionnaires. The study population numbered 808 members and 100 of whom were sampled. The selected sample of Purporsive Sampling with the criteria set by saving at least 5 months old and all members of the cooperative blessing respondents who self-sufficient savings and loans. Technical analysis is the analysis of the data used servqual score = score of expectation-perception score is calculating the difference or (Gap) to determine the quality of service. Of the five dimensions of service quality Restu Cooperative of Self-reliance can be concluded that the positive savings and loan service users are not satisfied with the quality of service cooperatives Restu Berdikari for service quality Servqual score of 0.37 was obtained. The analysis showed that the expected value is greater than the perceptions of members of the cooperative, means a greater quality of service expectations than on reality. The results of this study indicate members' responses to service quality Restu Berdikari Cooperative shows that most responding dissatisfied. Items that are greatest difference is the responsiveness of the employees of cooperatives is 0.66.Keywords: Service Quality, Koperasi Restu Berdikari, Kabupaten Sintang